Case Report: Canakinumab for the Treatment of a Patient With COVID-19 Acute Respiratory Distress Syndrome - Caracciolo, Massimo; Macheda, Sebastiano; Labate, Demetrio; Tescione, Marco; La Scala, Stefano; Vadalà, Eugenio; Squillaci, Rosalba; D’Aleo, Francesco; Morabito, Antonella; Garreffa, Cristina; Marciano, Maria Concetta; Oliva, Esther N. (Frontiers in Immunology, 2020)
Severe cases of COVID-19 present with serious lung inflammation, acute respiratory distress syndrome and multiorgan damage. SARS-CoV-2 infection is associated with high cytokine levels, including interleukin-6 and certain subsets of immune cells, in particular, NK, distinguished according to the cell surface density of CD56. Cytokine levels are inversely correlated with lymphocyte count, therefore cytokine release syndrome may be an impediment to the adaptive immune response against SARS-CoV-2 infection. Canakinumab, a monoclonal antibody targeting IL-1β is under investigation for the treatment of severe SAR-CoV-2 infection. An 85 year old male presenting in our hospital with COVID-19, whose condition was complicated by acute respiratory distress syndrome and cardiac and renal failure (with oliguria) after 25 days of hospitalization, was intubated and received canakinumab for compassionate use. On the next day, diuresis recovered and conditions improved: high IL-6 levels and NK cells expressing CD56bright (associated with cytokine relase) were significantly reduced giving rise to NK CD56dim. Patient died on day 58 with pulmonary bacterial superinfection and persistent SARS-CoV-2 positivity. In conclusion, canakinumab rescued a high risk, very elderly patient, from multiorgan damage complicating COVID-19. It may represent an useful treatment in severe cases.